A Translation Procedure Analysis of Simple Sentence in Novel Negeri Lima Menara by A. Fuadi - Frihatmawati, Rizky (Sekolah Tinggi Bahasa Asing JIA, 2023)
The paper was aimed at finding out what kind of the translation procedures used in simple sentence in Negeri Lima Menara novel, how they were applied in translation, and also finding out the most dominan procedure used in the translation. The writer took 50 data from Negeri Lima Menara’s novel and its translation. This research used a qualitative method. Firstly the writer searched the simple sentences in the original novel and compared to its translation, then she determined kinds of procedure used in the translation by comparing to the original one such as the change of structure and content of meaning after the process of translation. The writer concluded that from sixteen translation procedure, the translator used ten procedures in simple sentence’s translation. They were literal translation (15), modulation (11), transposition (8), expansion (4), reduction (4), transference (3), descriptive equivalent (2), cultural equivalent (1), functional equivalent (1), and couplet (1). Literal translation was the most dominant procedure in this translation. This procedure was commonly applied when SL had literally equivalent replacement in the TL. It happened because of the similarity of the simple sentence patterns in both SL and TL. Meanwhile, the translator used other translation procedures since she found the cultural words, the diffrences of grammatical structure, and the context of perception.